2010
DOI: 10.2135/cropsci2009.03.0129
|View full text |Cite
|
Sign up to set email alerts
|

Response of Oat Genotypes to Fusarium Head Blight in Eastern Canada

Abstract: Recent investigations in northern Europe and western Canada suggested that mycotoxins caused by Fusarium head blight (FHB) could be a potential problem for oat (Avena sativa L.) production and oat food safety. Here we report studies conducted in eastern Canada to address this issue. In one study, oat genotypes of diverse origin were evaluated for grain and groat deoxynivalenol (DON) contamination owing to artificial FHB inoculation at Ottawa, ON, in 2006 and 2007. In a separate study, oat genotypes tested in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 13 publications
5
32
0
1
Order By: Relevance
“…Многие исследователи отмечают, что голозерные со-рта овса более устойчивы к поражению зерна грибами и меньше накапливают микотоксины (Gavrilova et al, 2008;Tekauz et al, 2008;Yan et al 2010;Gagkaeva et al, 2013). При инокуляции растений грибами Fusarium основ-ные элементы урожайности -масса 1 000 зерен и масса зерна с метелки -уменьшались у пленчатых европейских сортов по сравнению с голозерными (Kiecana et al, 2002;Mielniczuk et al, 2004).…”
unclassified
“…Многие исследователи отмечают, что голозерные со-рта овса более устойчивы к поражению зерна грибами и меньше накапливают микотоксины (Gavrilova et al, 2008;Tekauz et al, 2008;Yan et al 2010;Gagkaeva et al, 2013). При инокуляции растений грибами Fusarium основ-ные элементы урожайности -масса 1 000 зерен и масса зерна с метелки -уменьшались у пленчатых европейских сортов по сравнению с голозерными (Kiecana et al, 2002;Mielniczuk et al, 2004).…”
unclassified
“…A number of authors have reported that FHB lowers grain yield and quality; the fungi also produce deoxynivalenol (DON), zearalenone and HT-2 mycotoxins in kernels, which are harmful to livestock and pose a safety concern in human food (Placinta et al 1999;Clear et al 2000;Bottalico and Perrone 2002;Parikka et al 2008;Tamburic-Ilincic 2010). Consequently, there has been an increase in disease awareness and the development of management strategies to mitigate the adverse effects of FHB on oats (Gavrilova et al 2008;Tekauz et al 2008;Yan et al 2008Yan et al , 2010. Several Fusarium species including F. acuminatum Ellis and Everhart, F. avenaceum (Corda: Fr.)…”
mentioning
confidence: 99%
“…Although FHB severity can be reduced or controlled by foliar fungicide applications, the use of genetic resistance is considered as one of the most practical and environmental measures for disease management Tekauz et al 2008;Yan et al 2008Yan et al , 2010. High levels of resistance to FHB have been identified in oat germplasm and considerable breeding has been conducted to develop resistant cultivars and lines (Gavrilova et al 2008;Tekauz et al 2008;Yan et al 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations